Membership inference attack and defense method in federated learning based on GAN - Jiale ZHANG; Chengcheng ZHU; Xiaobing SUN; Bing CHEN (Tongxin xuebao)
Aiming at the problem that the federated learning system was extremely vulnerable to membership inference attacks initiated by malicious parties in the prediction stage, and the existing defense methods were difficult to achieve a balance between privacy protection and model loss.Membership inference attacks and their defense methods were explored in the context of federated learning.Firstly, two membership inference attack methods called class-level attack and user-level attack based on generative adversarial network (GAN) were proposed, where the former was aimed at leaking the training data privacy of all participants, while the latter could specify a specific participant.In addition, a membership inference defense method in federated learning based on adversarial sample (DefMIA) was further proposed, which could effectively defend against membership inference attacks by designing adversarial sample noise addition methods for global model parameters while ensuring the accuracy of federated learning.The experimental results show that class-level and user-level membership inference attack can achieve over 90% attack accuracy in federated learning, while after using the DefMIA method, their attack accuracy is significantly reduced, approaching random guessing (50%).